POstpartum plasma profile of total cholesterol and triglycerides in Holstein Friesian cows with and without hormone therapy under tropical climate - PATEL, P M; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
Twenty-four HF cows of University farm were monitored through clinical diagnosis and weekly plasma profile oftotal cholesterol and triglycerides from the day of calving till 21" week postpanum. This was done in conceived and nonconceivedanimals, and with and without GnRH (Receptal) and PGF2a (Lutalyse) treatment at 7"" week postpartum inanoestrus and suboestrus cows (6 each), respectively. The mean cholesterol concentration of GnRH and PGF2a groups didnot differ significantly (93.98±1.87 vs 99.89±1.90 mg/di) between weeks or between groups at any of the intervalspostpartum. It was significantly higher in GnRH treated group than the control group at IO'b to 141b week postpartum;Further, the concentration in GnRH treatment, control and pooled groups was low at calving, which declined a little at I"week, and then increased linearly and significantly to reach the highest level by 14"'-171• week postpanum in three groups,and then declined insignificantly till 21" week postpartum, however in PGF ,a groups, the weekly means fluctuatedinsignificantly. Moreover, the values of cholesterol were significantly higher in PGF2a treated than control group only at3rd and 4"' week postpartum. The weekly mean cholesterol concentrations of conceived and non-conceived cows and theirpooled group fluctuated highly significantly (P < 0.01) between weeks postpartum from 62.40±9.19 to 115.27±6.79 mg/di,but not between groups at any of the intervals postpartum. The animals that conceived had relatively low cholesterol duringearly postpartum period and it increased significantly by 4th week and funher by 19th week postpartum compared to nonconceivedgroup. The weekly mean plasma triglycerides levels in cows of GnRH group were higher than those of PGF2agroup almost throughout the postpartum period with significant (P < 0.05) difference at I", 151• and 19"' week postpartum,including the overall means (52.68±1.17 vs 43.15±1.43 mg/di). However in GnRH and PGF2a treatnit~t, control and theirpooled groups as well as in conceived and non-conceived groups it neither varied significantly between weeks nor betweengroups at any of the intervals postpartum. Triglycerides levels were little low at calving, then got slightly elevated from 5111 -6"' week postpanum and again showed slight declining values from 13111-14"' week till 21" week postpartum in all the groups.Moreover, the levels were higher in PGF2a control than the treatment group throughout postpartum period, but variedsignificantly only at 3rd, 4•• and 81" week. The overall mean triglycerides concentrations of GnRH and PGF2a treated cowswere significantly lower (P < 0.01) than their controls (48.18±1.01 vs 56.96±2.08 and 33.48±1.43 vs 53.06±2.26 mg/di),but the values of conceived and non-conceived groups did not vary significantly (50.36±1.59 vs 46.94±1.18 mg/di).
Keywords: Holstein Friesian cows; hormone therapy; cholesterol; triglyceride; postpartum period